THE ROLE OF COMMUNITY IN SAFEGUARDING THE HISTORY OF DENPASAR - Ni Ketut Ayu Siwalatri (Jurnal Pengembangan Kota, 2019)
Denpasar has a variety of heritage assets that are still used by the people. Living Culture or intangible cultural heritage refers to the practices, representations, expressions, knowledge, and skills owned by the local community. Globalization and information technology are factors that influence people to change and reinterpret their traditions that have been carried out for generations. This paper aims to explore the role and rights of the community in safeguarding their architecture and the built environment. From this study can be concluded that the changes made to the architecture and built environment are mostly carried out by following the current trends as a representation of the economic capacity of the owner and sometimes ignoring the rules and knowledge/tatwa and norm/susila that were previously used by the community for the spatial arrangement of their environment. In the past, knowledge was possessed by Brahmins in the power of the king, and the people only carry out traditions with little knowledge of the meaning contained in it. The knowledge stored in artifacts needs to be socialized or published so the changes made are still rooted in the local cultural character and can maintain the identity of the city of Denpasar.